A morphological study to evaluate variations of foramen transversarium in atlas vertebrae- An Original Research - Chopade, Dr.DnyandeoKisan (International Journal of Psychosocial Rehabilitation, 2009)
Background: The only ring shaped cervical vertebra present in human body is atlas, having articulations with occipital and axis vertebra. Present study aimed to find incidence and clinical correlation of accessory foramen transversarium in cervical vertebrae.Material and method: 100 dried macerated atlas vertebrae of both the sexes from various bone banks of region were obtained for the study of accessory foramen transversarium.Results: All the 100 atlas vertebrae which were studied showed presence of foramen transversarium as a characteristic feature of cervical vertebra. Out of total, 25 (25.0%) had accessory foramina on the posterior arch. When studied for further detail it was found that out of these 10 had it bilaterally whereas 9 on right side and 6 on left side only. Maximum accessory foramens were found to be extended side to side elliptical in shape (i.e. 66%) whereas oval (15.0%) and vertical elliptical (18.0%) shape too was there. The right sided foramens were with larger sizes as compared to left sided ones and in 28.3% cases they were even of the size of Foramen transversarium.Conclusion: This study is important for clinician/ surgeons to understand incidence, variation and importance of accessory foramen transversarium and its clinical importance to avoid misdiagnosis in their clinical practice.